1984
DOI: 10.2527/jas1984.5961467x
|View full text |Cite
|
Sign up to set email alerts
|

Sire × Environment Interactions for Growth Traits of Hereford Cattle

Abstract: Twelve Hereford bulls were used to sire calves in each of three locations in North Carolina over 6 yr. Three bulls were bred artificially to a random one-third of the cows at each location each year. Locations represented the Mountain, Piedmont and Coastal Plain regions of the Southeast. As yearlings, steer progeny were fed a concentrate diet in a feedlot or grazed on pasture and then slaughtered in the fall. Performance records from 816 calves were used to evaluate sire X location interaction effects for birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2
3

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
5
2
3
Order By: Relevance
“…In contrast to the two previous studies, a study of Hereford sired calves born in three different location across North Carolina over a six year period revealed no sire by environment interaction (Tess et al, 1984).…”
Section: Beef Cattlecontrasting
confidence: 90%
See 2 more Smart Citations
“…In contrast to the two previous studies, a study of Hereford sired calves born in three different location across North Carolina over a six year period revealed no sire by environment interaction (Tess et al, 1984).…”
Section: Beef Cattlecontrasting
confidence: 90%
“…Phase two, experimental design as described previously, showed that M1 and F4 had different Weaning weight differed between crossbred and purebred calves in which crossbred animals were on average 15 kg heavier in the first study and on average 27 kg heavier in the second study compared to purebred calves (Northcutt et al, 1990). While these results would show strong genotype by environment interaction, other studies have shown no significance (Tess et al, 1984). It was reported by Tess et al (1984) that no significant sire x location interactions were present for birth weight, preweaning average daily gain, and weaning weight in North Carolina among three locations (Mountain, Piedmont, and Coastal Plain regions of the Southeast).…”
Section: Beef Cattlementioning
confidence: 63%
See 1 more Smart Citation
“…Burns et al (1979) reported significant G×E for birth and weaning weights for cattle produced and reared in Florida versus Montana, highly divergent environments. Conversely, Tess et al (1984) found little evidence for G×E for the same traits in cattle produced and reared in different locations within North Carolina, a more limited range of environments.…”
Section: Introductionmentioning
confidence: 98%
“…Environments are usually distinguished according to country, state, or region (Tess et al, 1984;Bertrand et al, 1987;Lopes et al, 2008). A multivariate exploratory approach that groups specific regions into clusters based on their climatic, geographic characteristics, or both is a suitable alternative for defining environments as demonstrated by Weigel and Rekaya (2000) and Ravagnolo and Misztal (2002).…”
Section: Introductionmentioning
confidence: 99%